Review of Community Pharmacy Staff Educational Needs for Supporting Mental Health Consumers and Carers - Mey, A.; Fowler, J.; Knox, K.; Shum, D.; Fejzic, J.; Hattingh, Laetitia; McConnell, D.; Wheeler, A. (Springer New York LLC, 2014)
Development of a mental health education package for community pharmacy staff should be informed by mental health consumers/carers’ needs, expectations and experiences, and staff knowledge, skills and attitudes. This review (1) explored research on community pharmacy practice and service provision for mental health consumers/carers, and (2) identified validated methods for assessing staff knowledge, skills and attitudes about mental illness to inform the development of a training questionnaire. A literature scan using key words knowledge, skills, attitudes, and beliefs combined with community pharmacy, pharmacist, and pharmacy support staff, and mental illness, depression, anxiety was conducted. A small number of studies were found that used reliable methods to assess pharmacists’ training needs regarding mental illness and treatment options. There was little published specifically in relation to depression and anxiety in community pharmacy practice. No studies assessed the training needs of pharmacy support staff. A systematic analysis of pharmacy staff learning needs is warranted.